PERTANGGUNGJAWABAN HUKUM BANK YANG MENGHILANGKAN DOKUMEN SURAT KEPUTUSAN PENGANGKATAN PEGAWAI NEGERI SIPIL SEBAGAI JAMINAN KREDIT - Putri, Ela Andini; Yahanan, Annalisa (Lex LATA, 2024)
In practice, the Civil Servant Appointment Decree can be used as credit guarantee, but sometimes there are banks as creditors (guarantors) have lost the Decree, thus causing losses to customers as debtors. The aim of this research is to explain and analyze the judge's legal considerations and liability of the Bank for losing credit guarantee documents based on Mataram District Court Decision Number 245/Pdt.G/2018/PN.Mtr. This research is normative legal research, with a collecting legal materials technique obtained from literature studies. The result of this research indicates that the standing of the Civil Servant Appointment Decree in Indonesian guarantee law is that it is not a form of guarantee according to general guarantees and special guarantees which consist of material guarantees and individual guarantees. However, the Bank accepted the Civil Servant Appointment Decree as credit guarantee for civil servants through a credit agreement, on the grounds that it had economic value, because the Bank was given a power of attorney from the debtor's office to deduct the debtor's salary. Regarding the judge's legal considerations, this was because the Bank as the Defendant had committed an unlawful act in the form of negligence which caused the Plaintiff to no longer have the opportunity to use his Civil Servant Appointment Decree as guarantee for credit at another Bank in the future, and therefore, the Defendant was obliged to take responsibility for his negligence by replacing losses suffered by the Plaintiff. Regarding the Bank's liability, it is declared negligent for committing an unlawful act with a penalty of compensating for the losses suffered by the Plaintiff and the potential for administrative sanctions in the form of fines, written warnings, suspension of certain business activities, and revocation of business permits by the Management of Bank Indonesia, including the potential for imprisonment and fines against the Board of Directors or bank employees if they are proven to have intentionally lost the documents